PHYSICO-CHEMICAL, PHYTOCHEMICAL AND HPTLC ANALYSIS OF THE WHOLE PLANT OF ORTHOSIPHON THYMIFLORUS (ROTH.) SLEESEN - S, Mercy Lavanya; A, Gnanamani; R, Ilavarasan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The plant Orthosiphon thymiflorus (Roth.) sleesen is an herb belonging to the family Lamiaceae. It has been reported to possess several pharmacological properties. The study was aimed at carrying out the physico-chemical, phytochemical and high-performance thin layer chromatography (HPTLC) analysis on the whole plant of O. thymiflorus. Methods: The physico-chemical parameters were tested using standard methods. The preliminary tests for phytochemicals present were tested using conventional methods. CAMAG HPTLC system equipped with TLC autosampler 4 applicator, TLC scanner 3 and win CATS 1.4.4. software was used for HPTLC analysis of the plant. The different extracts were developed using suitable mobile phases using standard procedures and scanned under ultraviolet 254 nm. The plates were also viewed under 366 nm and after derivatization with vanillin-sulfuric acid. Results: The physico-chemical parameters were studied. The plant was found to be free from adulteration and contamination. On phytochemical analysis, the plant showed the presence of triterpenoid, flavonoid, alkaloid, phenol, steroid, sugars, quinone and coumarin in different extracts tested. The TLC plate showed several spots at different Rf when viewed under 254 nm, 366 nm and after derivatization with vanillin-sulfuric acid. The HPTLC profile showed several peaks that indicated the presence of various phytochemicals present in the plant. Conclusion: The study will help in standardization of the plant. The HPTLC profile will help in authentication and standardization of the plant. Keywords: Orthosiphon thymiflorus, High performance thin layer chromatography, Phytochemical screening, Standardization.